2008
DOI: 10.1111/j.1600-6143.2008.02353.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Islet Transplantation

Abstract: Islet cell transplantation has recently emerged as one of the most promising therapeutic approaches to improving glycometabolic control in diabetic patients and, in many cases, achieving insulin independence. Unfortunately, many persistent flaws still prevent islet transplantation from becoming the gold standard treatment for type 1 diabetic patients. We review the state of the art of islet transplantation, outcomes, immunosuppression and-most important-the impact on patients' survival and long-term diabetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
150
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 38 publications
0
150
0
3
Order By: Relevance
“…Considering that intensive treatment with exogenous insulin only delays the occurrence of T1D complications, more strategies have been explored to improve outcomes of patients with T1D. To date, islet cell transplantation, pancreas transplantation, and anti-CD3 mAb administration have been authorized for clinical use (9,16,17). Although pancreas transplantation achieved insulin independence in 60% of subjects at 4 years after the transplant (with a median graft survival time of 9 years, according to the United Network for Organ Sharing data registry analysis), the surgical procedure is still associated with a substantial mortality rate (78% of individuals survived at 1 year) (18).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that intensive treatment with exogenous insulin only delays the occurrence of T1D complications, more strategies have been explored to improve outcomes of patients with T1D. To date, islet cell transplantation, pancreas transplantation, and anti-CD3 mAb administration have been authorized for clinical use (9,16,17). Although pancreas transplantation achieved insulin independence in 60% of subjects at 4 years after the transplant (with a median graft survival time of 9 years, according to the United Network for Organ Sharing data registry analysis), the surgical procedure is still associated with a substantial mortality rate (78% of individuals survived at 1 year) (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the question of whether longterm diabetes complications are halted or reversed by islet transplantation is still not fully known. Studies from other groups have shown that restoration of islet function may improve quality of life, decrease the number of hypoglycaemic episodes and be potentially protective against longterm complications in diabetic patients [24].…”
Section: Introductionmentioning
confidence: 99%
“…A utoimmune type 1 diabetes (T1D) results from autoimmune attack on insulin-secreting β cells and subsequent insulin deficiency (1). Cure of T1D requires both reversal of autoimmunity and resupply of insulin-secreting β cells by islet transplantation or augmentation of endogenous β-cell regeneration (2). Because of the lack of donors for islet transplantation and because islet grafts only last for ∼3 y (3), augmentation of endogenous β-cell regeneration would be the more favorable approach.…”
mentioning
confidence: 99%